2016
DOI: 10.1159/000443538
|View full text |Cite
|
Sign up to set email alerts
|

The Posterior Limb of the Internal Capsule as the Subcortical Transitional Zone of the Anterior and Posterior Circulations: Insights from Human 7T MRI

Abstract: Background: In patients with cerebral infarction, identifying the distribution of infarction and the relevant artery is essential for ascertaining the underlying vascular pathophysiological mechanisms and preventing subsequent stroke. However, visualization of the basal perforating arteries (BPAs) has had limited success, and simultaneous viewing of background anatomical structures has only rarely been attempted in living human brains. Our study aimed at identifying the BPAs with 7T MRI and evaluating their di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In contrast with the PLIC, the relationship between swallowing and the caudate nucleus is unclear. While further research is needed, it should be noted that these two regions receive similar blood supply [24].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the PLIC, the relationship between swallowing and the caudate nucleus is unclear. While further research is needed, it should be noted that these two regions receive similar blood supply [24].…”
Section: Discussionmentioning
confidence: 99%
“…It possible that specific anatomic characteristics provide the foundation for hemorrhagic progression. Since projection fibers are primarily located in the internal capsule, and are most abundant in the PLIC ( 23 ), blood to the PLIC region is supplied by branches from multiple arteries ( 24 ). One large study has also indicated that hematoma involving the PLIC is strongly correlated with a worse prognosis ( 13 ), and that HE itself is a critical predictor of ICH outcome ( 3 ), which underlines the potential link between the PLIC and HE.…”
Section: Discussionmentioning
confidence: 99%
“…Stems were defined as LSAs that originated directly from the ACAs or MCAs. The branches were defined as daughter vessels originating from the parent LSA stems, without any subordinate branches (single vessels) (21, 22). If the trunk had no branches, it was recorded as both stem and branch (Supplementary Figure 1).…”
Section: Methodsmentioning
confidence: 99%